Dental Caries Preventive Considerations: Awareness of Undergraduate Dental Students - Hani M. Nassar (MDPI AG, 2020)
The aim of this study was to assess awareness and knowledge of undergraduate dental students of common caries-related preventive considerations and to highlight these factors in a concise manner to act as a guide for dental practitioners. A sample of 118 undergraduate students at a local government dental school was included. An interactive survey that contains questions related to common preventive strategies against dental caries was presented to the students. The survey contained 22 questions concerning dietary and therapeutic strategies. Students casted their votes using their mobile cellphones. The correct answer for each question was shown to the students, and further discussion was held. Data was collected, and the statistical analysis was conducted using one-sample z- and chi-squared tests at 0.05 significance level. The students answered the questions related to oral hygiene practices, xylitol, and the common knowledge regarding fluoride. The questions related to the use of chlorhexidine, dietary factors, and fluoride formulations were answered mostly incorrectly. The students seemed to grasp details of important concepts of flossing, brushing, reducing frequency of sugar exposure, and the use of fluoride products. Still, more emphasis should be given to increase students' awareness of dietary guidelines for caries prevention, since adequate knowledge of these modalities is paramount for graduating dentists.